Multifunctional modular system: children’s furniture for ages 3 to 9 (REVISTA NODO, 2013)
The article addresses the issue of children’s furniture in Colombia. It points out the design deficiencies found in most products currently offered in the market (usefulness for just one or two functions at the greatest, fast obsolescence and high environmental impact), in comparison with those designed in Europe and North America: versatile, multifunctional, built with recycled materials, simple yet efficient, among others. It traces a typical profile of direct and indirect users (children and parents/tutors, respectively), and defines the usual activity zones for kids between 3 to 9 years of age in order to identify the specific functions demanded on their furniture and to determine design strategies and guidelines. Finally, it presents Magoo Modular System, its product concept, its differential value, its design process and its materials. It concludes that multi-functionality and flexibility, versatility and transformation capability are all essential when designing children’s furniture.
Keywords: Children’s furniture; recycling; flexibility; multi-functionality